Circular RNA SNX27 Facilitates Gastric Cancer Progression By Sponging miR-638 - Xi, Yanfeng; Gai, Yu; Zhang, Weixing; Wang, Meihua; Liu, Qian; Bi, Yanzhi (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Accumulating evidences have shown an important role of circular RNAs (circRNAs) in the tumorigenesis of gastric cancer (GC). Nevertheless, whether circSNX27 plays a role in GC remains undetermined. Materials and Methods: Relative expression of circRNAs and related microRNAs (miRNAs) in GC tissues and cells were tested by quantitative reverse transcription polymerase chain reaction. Specific short hairpin RNAs were designed to knockdown the expression of circSNX27 in GC cells. CCK-8, colony formation, flow cytometry, wound healing, and transwell assays were used to access the function of circSNX27 silencing on GC cells. The target miRNAs of circSNX27 were predicted by 2 databases, circBank and Circinteractome. Dualluciferase reporter assay was used to verify the interaction between circSNX27 and miR-638. Results: circSNX27 was found to be upregulated in GC tissues and cell lines compared with normal controls. Silencing of circSNX27 repressed GC cell viability, proliferation, migration, and invasion. Moreover, circSNX27 silencing could accelerate GC cell apoptosis. Additionally, we found that circSXN27 decreased the expression of miR-638 by directly binding to it in GC cells. Conclusion: Our results indicated that circSXN27 facilitated GC progression by acting as a sponge of miR-638. Cite this article as: Xi Y, Gai Y, Zhang W, Wang M, Liu Q, Bi Y. Circular RNA SNX27 facilitates gastric cancer progression by sponging miR-638. Turk J Gastroenterol. 2024;35(4):280-287.